A ironia machadiana: uma análise do conto “A igreja do diabo” - RIBEIRO, Renata Silva (2022)
The present work treats about Machado's irony, through a brief analysis of the short story “The devil’s Church”, which was published in 1884, in the book of short stories entitled “Undated Stories”. The aim is to discuss the use of irony in Machado's short story “The devil’s Church”. The authors who served as theoretical references Montello (1972, Veríssimo (1981) and Coutinho (1959 and 1969), among others. This work follows the guidelines of a bibliographical research. For that, the corpus used was the Machado’s short story “The devil’s Church.” Machado de Assis' short story will be analyzed in order to find in which parts of the text the writer uses irony. The results reveal that Machado’s short story is covered irony, very memorable feature in Machado’s writing. It follows that the writer has a brilliant contemporary vision and his impressionist literature about this "war" of God and the Devil, of good and evil, the irony of the reversal of values, the eternal human contradiction. Then, verifying the extremely refined irony in this work, reveal the incredible capacity of a writer, of a very elegant style that reveals an acute perception of human nature and life.